MENINGKATKAN KEMAMPUAN MEMBACA DAN MENULIS PERMULAAN MELALUAI KEGIATAN LITERASI DENGAN MEDIA BUKU ANAK DI TKIT BINA PRESTASI - Elis Mayasri (LPPM Universitas Bina Bangsa, 2023)
Departing from the author's anxiety in addressing whether or not teaching reading and writing is applied to early childhood at the kindergarten level and the way teachers apply teaching methods to read and write to early childhood, the authors conducted classroom action research at TKIT Bina Prestasi, Tangerang City in 2022/23 school year. This study aims to improve initial reading and writing skills through literacy activities using children's book media at TKIT Bina Prestasi, Periuk, Tangerang city, in the 2022/23 academic year. This research is class action research or PTK. The subjects in this study were group B children of TKIT Bina Prestasi, Periuk, Tangerang City, with a total of 7 children consisting of 4 boys and 3 girls. The object of this research was the ability to read and write beginning through literacy activities using children's book media. The method used in this research is descriptive research method with a qualitative approach, with research instruments using observation sheets and documentation. The data analysis technique uses descriptive percentages in three phases, namely the stage before corrective action (pre-cycle), and after the action from Cycle I to Cycle II where cycles I and II are carried out within 5 days each. The results of the study showed that the initial reading and writing skills through literacy activities using children's book media in group B at TKIT Bina Prestasi could be carried out very well. This can be proven by an increase in the completeness and enthusiasm of children's learning, from pre-action to cycle II, where the results of the pre-action reading reached 32.1% and 35.7% writing, the results of the first cycle the average reading ability reached 49.6%. and writing 48.9% and an average performance of 52.2%, the results of cycle II average reading ability reached 77.5% and 77.2% writing and an average performance of 79.7%. The research was stopped until cycle II because it had fulfilled the success indicators and the children's learning completeness had increased very satisfactorily